Mathematical Progress in Expressive Image Synthesis III Selected and Extended Results from the Symposium MEIS2015 - Dobashi, Yoshinori; Ochiai, Hiroyuki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
"Progress in Expressive Image Synthesis" (MEIS2015), was held in Fukuoka, Japan, September 25-27, 2015. The aim of the symposium was to provide a unique venue where various issues in computer graphics (CG) application fields could be discussed by mathematicians, CG researchers, and practitioners. Through the previous symposiums MEIS2013 and MEIS2014, mathematicians as well as CG researchers have recognized that CG is a specific and practical activity derived from mathematical theories. Issues found in CG broaden the field of mathematics and vice versa, and CG visualizes mathematical theories in an aesthetic manner. In this volume, the editors aim to provoke interdisciplinary research projects through the peer-reviewed papers and poster presentations at the this year's symposium. This book captures interactions among mathematicians, CG researchers, and practitioners sharing important, state-of-the-art issues in graphics and visual perception. The book is suitable for all CG researchers seeking open problem areas and especially for those entering the field who have not yet selected a research direction.
Part I Geometry -- Geometry and Mechanics of Fibers: Some Numerical Models -- Tetrisation of Triangular Meshes and Its Application in Shape Blending -- A Construction Method for Discrete Constant Negative Gaussian Curvature Surfaces -- Fabrication-Aware Geometry Processing -- Part II Artificial Animation -- Revisiting Vorticity: Pushing Fluid Solvers to the Next Level -- Active Comicing for Freehand Drawing Animation -- A Multilayered Model for Artificial Intelligence of Game Characters as Agent Architecture -- Part III Illusion, Patterns, and Visualization -- Visual Media Culture Supported by Human Depth Illusion -- Wang Tile Modeling of Wall Patterns -- High-Resolution Visualization Library for the Exascale Supercomputer -- Part IV Curves -- Drawing Curves -- Aesthetic Design with Log-Aesthetic Curves and Surfaces -- Attractive Plane Curves in Differential Geometry -- dNLS Flow on Discrete Space Curves -- Index.
Keywords: Engineering mathematics; Engineering -- Data processing; Image processing -- Digital techniques; Computer vision; Computer science -- Mathematics; Computer-aided engineering; Mathematical and Computational Engineering Applications; Computer Imaging, Vision, Pattern Recognition and Graphics; Mathematical Applications in Computer Science; Computer-Aided Engineering (CAD, CAE) and Design